PEACOCK MODEL PEDAGOGY: INTERVENTION AND INNOVATIVE CATALYST IN THE NEW NORMAL PERSPECTIVE OF TEACHING AND LEARNING - MALLILLIN, LEOVIGILDO LITO D.; LAUREL, REGILITO D.; ARROYO, PILIPINAS AMERICA C.; MALLILLIN, JOCELYN B. (Innovare Journal of Education, 2021)
The study aims to analyze and identify how peacock model pedagogy improves the intervention and innovation catalyst in the new normal perspective of teaching and learning among the respondents. The study employs both a descriptive quantitative and qualitative research approach and design because it is used in analysing the intervention and innovative catalyst in the new normal perspective of teaching and learning. Purposive sampling is utilized in gathering the sample size of the study. It is a selection of intentional formats based on the concept that elucidates the specific theme or phenomenon of the study. This study comprised thirty six (36) respondents. Results show that students are actively participating and developing quality of leadership and initiative and are actively participating through exchange of ideas and interactions in the peacock model pedagogy on innovation of teaching and learning, participation, with a weighted mean of 4.06 or Agree which shows that students are actively participating and developing quality of leadership and initiative and are participating actively through exchange of ideas and interactions, questioning and experimentation, with a weighted mean of 3.66 or Agree which shows that students are able to frame learning related questions and inquisitive lessons for discussion and are able to frame learning related questions but have difficulties in exploring to answer the question raised among them, empathy and cooperation, with a weighted mean of 3.75 or Agree which shows that students are empathetic towards both the known and unknown persons in the pedagogy of learning in the new normal and are actively empathetic towards the known but only sympathetic towards the unknown process of learning, aesthetic and creative expression of knowledge, with a weighted mean of 3.75 or Agree which shows that students are aesthetic and creative in their new normal learning perspective pedagogy and are aesthetic and creative in their online classes as part of their innovative learning perspective. Findings show that there is a significant difference in the peacock model pedagogy that improves the intervention and innovation catalyst in the new normal perspective of teaching and learning as observed by the respondents.